Small molecules as kinetoplastid specific proteasome inhibitors for leishmaniasis: a patent review from 1998 to 2021. (4th May 2022) - Imran, Mohd; Khan, Shah Alam; Abida,; Alshrari, Ahmed Subeh; Eltahir Mudawi, Mahmoud Mudawi; Alshammari, Mohammed Kanan; Harshan, Aishah Ali; Alshammari, Noufah Aqeel
ABSTRACT: Introduction: Leishmaniasis is a neglected tropical infectious disease. The available limited therapeutic options for leishmaniasis are inadequate due to their poor pharmacokinetic profile, resistance, toxicity, high cost, and compliance problems. This warrants identification of new targets for the development of safer and effective anti- Leishmania therapy. The kinetoplastid specific proteasome (KSP) is a novel validated target to develop drugs against leishmaniasis. Area covered: This review focuses on all the published patent applications and granted patents related to the studied small molecules as KSP inhibitors (KSPIs) against Leishmania from 1998 to 31 December 2021. Expert opinion: A little amount of work has been done on KSPIs, but the study results are quite encouraging. LXE408 and GSK3494245 are two KSPIs in different phases of clinical trials. Some other small molecules have also shown KSP inhibitory potential, but they are not in clinical trials. The KSPIs are promising next-generation orally active patient compliant drugs against kinetoplastid diseases, including leishmaniasis. However, the main challenge to discover the KSPIs will be the resistance development and their selectivity against the proteasome of eukaryotic cells.